As manifestações do vazio na sociedade contemporânea - Langaro, Flávia Nedeff (Universidade do Vale do Rio dos Sinos, 2012)
Over the years, narcissist characteristics have increased, suggesting that young people today are more narcissistic than the young adults of previous generations. The fact is due to changes in contemporary society and to the interference of culture on personality. Narcissism is a psychoanalytic construct and is responsible for protecting the "I" and adjusts the subject's self-esteem. Among the various measures of narcissism developed, the Narcissistic Personality Inventory (NPI) has been the instrument most used in empirical studies, evaluating normal narcissism, ie, non-defensive and well resolved. Thus, this study sought to identify the narcissistic personality characteristics in 350 young adult college students, by gender, age and type of college of these young people, as well as perform an initial analysis of the psychometric properties of the NPI. This study took a quantitative design, transversal. Data analysis was performed using descriptive and inferential statistics, followed by the Student t test and ANOVA to identify mean differences between groups, as well as Exploratory and Confirmatory Factor Analysis of the NPI. As a result of the study, analysis of 14 the initial psychometric characteristics of the instrument showed a factor solution of six factors, which underscores the multidimensionality of the instrument and the need to specify aspects of hierarchical dimensions. Still, a more discriminating analysis shows that in relation to sex of participants, men had higher rates in NPI compared to women. As to the age, there weren´t significant differences in scores related to narcissism. Finally, regarding the areas of knowledge, university students of Exact Sciences courses showed higher narcissism scores than students of Human and Health Sciences.
Keywords: Narcisismo; Sociedade contemporânea; Inventário de personalidade narcísica (NPI); Narcissism; Contemporary society; Narcissistic personality inventory (NPI); ACCNPQ::Ciências Humanas::Psicologia